'Only the people can defend this struggle': the politics of the everyday, extrajudicial executions and civil society in Mathare, Kenya. Issue 154 (2nd October 2017) - Jones, Peris S.; Kimari, Wangui; Ramakrishnan, Kavita
ABSTRACT: Though a perennial problem in postcolonial Kenya, extrajudicial executions (EJE) show few signs of ending and in recent years are even accelerating amongst young men in informal settlements. Avenues for legal, institutional and civil society redress, nominally expanded in recent years, display an ongoing tendency towards disconnection from the grassroots. A case study from Mathare, Nairobi, seeks explanations for the lack of urgency in addressing EJE and also the limited effectiveness of responses to them that are rooted in the political economy of interests of civil society actors, which tends to perpetuate these 'excluded spaces' of the slum. The authors do so, however, by exploring one particular struggle to show how frustration with civil society is being used by social justice activists to articulate ideas of 'everyday' violence to mobilise for change that disrupts the apparent normalisation of EJE.